Profile of Students’ Creative Thinking Skills and Implementation of Free Inquiry in Senior High School - Faatehah, Putri; Lestari, Nurita Apridiana (Jurnal Pendidikan MIPA, 2021)
Abstract: This study aims to determine the profile of students' creative thinking skills and the implementation of inquiry free in schools. The descriptive research design used a qualitative approach and involved 31 high school students. The data were obtained from interviews, tests, and questionnaires. The data collection instruments used were (1) interview instruments with teachers, (2) test question sheets with indicators of creative thinking skills, namely fluency, flex ibility, originality, and elaboration, also (4) questionnaires. The results showed six students in the very creative, four in the creative, eight in the moderately creative, six in the less creative, and seven in the non-creative. Creative thinking skills in each category are fluency by 63%, flexibility by 48%, originality by 45%, and elaboration by 35%. The research concludes that the inquiry free learning model can be applied in schools to help improve students' creative thinking skills, especially on the elaboration indicator.Keywords: creative thinking, free inquiry, linear motion. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp292-304